Relationship between premenstrual syndrome and basic personality traits: a cross-sectional study - Arslantaş, Hülya; Abacigil, Filiz; ÇinakliI, Şule (São Paulo Medical Journal, 2018)
BACKGROUND: Although many studies have investigated premenstrual syndrome and related factors, there is still only a limited number of studies investigating the relationship between premenstrual syndrome and basic personality traits. This study was conducted to investigate the association between pre-menstrual syndrome and basic personality traits among university students. DESIGN AND SETTING: Cross-sectional analytical study conducted in a city in western Turkey. METHODS: The Premenstrual Syndrome Scale, the Basic Personality Traits Scale and a questionnaire on sociodemographic characteristics developed by the present researchers were applied to 490 female students at the College of Health Sciences of a state university. RESULTS: Premenstrual syndrome was more common among students living in rural areas (65.1%), students with chronic diseases (74.1%), students who suffered from menstrual cramps (61.1%), students who used cigarettes (72.1%) and students with alcohol intake (65.5%). In the final model of the logistic regression analysis, presence of pain during the menstrual period increased the risk of presence of PMS by a factor of 1.554 (95% confidence interval, CI: 1.033-2.336; P = 0.034) and high scores on the total basic personality traits scale increased it by a factor of 1.016 (95% CI: 1.002-1.030; P = 0.029). The prevalence of premenstrual syndrome was found to be higher among students who were less extrovert (P = 0.007) and less conscientious (P = 0.001); and among students with higher neuroticism (P = 0.000) and negative valance (P = 0.000). CONCLUSION: This study demonstrates that personality may be associated with premenstrual syndrome.